2023
DOI: 10.29303/jppipa.v9i1.2268
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Pedagogical Content Knowledge (PCK) Self-Efficacy of Pre-Service Physics Teachers: Redefining the Role of Influencing Factors

Abstract: Self-efficacy intervention in curriculum design is an effort to improve the quality of teaching practice for pre-service teachers. This research aims to redefine how pre-service teachers' self-efficacy changes through Physics Learning and Microteaching courses. Interventions are given by designing lectures with mastery of knowledge, guidance, teaching experience, and reflection on teaching experience. The intervention carried out 32 meetings (with a total of 67 hours) in 1 semester. The data collection techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Categorization is divided into five groups adapted from (Haryanto et al, 2023), as shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Categorization is divided into five groups adapted from (Haryanto et al, 2023), as shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…It is better if efforts increase prospective teachers' self-efficacy (Boz & Cetin-Dindar, 2021). Selfefficacy interventions in the curriculum can be carried out to improve the quality of future teacher-teaching practices (Haryanto et al, 2023). Self-efficacy in teaching science has a positive relationship with attitudes toward teaching science (Ecevit & Kıngır, 2022).…”
Section: Prospective Physics Teachers' Self-efficacy In Each Domainmentioning
confidence: 99%
“…Guru mengharuskan mampu dan paham dengan pilihan model pembelajaran yang sesuai dengan keadaan siswa serta fasilitas yang ada agar pemahaman dalam pembelajaran meningkat. Sejalan dengan penelitian Obizoba (2015) dan Alberida (2023), guru diharapkan mampu menetapkan model pembelajaran yang sesuai guna mengoptimalkan hasil belajar dan motivasi siswa serta pemahaman guru dengan pemilihan model yang tepat saat pembelajaran di sekolah.…”
Section: Pedagogical Knowledge (Pk) Guru Biologi Sma Se-kartasura Dal...unclassified
“…Of these, 107 participants provided complete responses, which were subsequently utilized. The pilot study aimed to secure a minimum sample size of 100 participants, as suggested by Hair et al (2010). Notably, no demographic data related to the participants was collected during the validity and reliability assessment of the scale.…”
Section: Samplementioning
confidence: 99%